“It was a foregone conclusion”: a qualitative study of women’s experiences and meaning-making of later-in-life abortion in Belgium - Kato Verghote; Nathalie Neeser; Tenzin Wangmo; Guido Pennings; Veerle Provoost (Sexual and Reproductive Health Matters)
Abortion is an indispensable healthcare service for women of all reproductive ages. Research on abortion is often focused on younger women, neglecting those who are closer to the end of their reproductive lifespan. This study presents findings from qualitative interviews with Belgian women who had an abortion at the age of 40 or older, conducted between May 2022 and April 2023. Using interpretative phenomenological analysis, we explored the experiences and decision-making processes of women who had abortions later in life. We identified three main themes. First, the women’s families were at the centre of their abortion decisions, with some women also presenting advanced age as a significant factor in their decision-making. This emphasis on age was connected to perceived social norms about appropriately timed childbearing. Second, the women experienced their unplanned pregnancies as both physically and emotionally demanding, and desired to terminate them as soon as possible. Some participants felt additional emotional burdens because of delays caused by the mandatory waiting period and/or busy schedules at abortion centres. Third, the women expressed feelings of self-blame for their unplanned pregnancies. This self-blame was closely tied to their expectation of social disapproval, which made them cautious to share their abortion experience with people in their social circle. This study enhances our understanding of the experiences and meaning-making of abortion in women of advanced reproductive age. It highlights the need to destigmatise the topic and the importance for professionals and researchers to consider family preservation and advanced reproductive age as potential factors shaping abortion decision-making.